Management of the Khulafaur Rasyidin Organization in the Codification of the Quran - Rizal Anshorudin (International Journal of Education Management and Religion, 2024)
This research aims to examine the management practices implemented by the Khulafaur Rasyidin caliphs in the process of codifying the Quran, from the perspective of modern management science. The background of this study focuses on the importance of understanding the managerial strategies used by early Islamic leaders in the context of managing resources and information that were crucial at that time. The method employed in this research is descriptive qualitative, utilizing a literature review approach. Data collection techniques were conducted through literature studies and documentation, allowing the researcher to gather relevant information from various sources. Data analysis was performed using descriptive analysis, aimed at describing and explaining the findings obtained. In this study, the management theory used is George R. Terry's theory, which emphasizes management functions such as planning, organizing, executing, and supervising. The results indicate that the Khulafaur Rasyidin caliphs applied very good and effective management in the codification of the Quran, which aligns with the principles outlined in Terry's theory. This reflects their ability to manage resources and information to achieve greater goals in the dissemination of Islamic teachings. Thus, this research provides new insights into the integration of classical and modern management, as well as emphasizes the importance of a systematic managerial approach in the context of Islamic history.